2016
DOI: 10.1111/jpg.12645
|View full text |Cite
|
Sign up to set email alerts
|

Oil Family Typing, Biodegradation and Source Rock Affinity of Liquid Petroleum in the Danish North Sea

Abstract: Variations in liquid petroleum compositions in the Danish

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…(v) the sulphur content is on average 0.07 wt%. The mixed oils/condensates with a clear coaly contribution (oil families 5D/E-B and 4B-D/E; Petersen et al, 2016) can likewise be identified by these geochemical parameters, although the characteristics are slightly less pronounced than in oils belonging to family 6D/E-F) ( Fig. 5; Table 1).…”
Section: Composition and Occurrence Of Coaly Hydrocarbons Oilmentioning
confidence: 86%
See 4 more Smart Citations
“…(v) the sulphur content is on average 0.07 wt%. The mixed oils/condensates with a clear coaly contribution (oil families 5D/E-B and 4B-D/E; Petersen et al, 2016) can likewise be identified by these geochemical parameters, although the characteristics are slightly less pronounced than in oils belonging to family 6D/E-F) ( Fig. 5; Table 1).…”
Section: Composition and Occurrence Of Coaly Hydrocarbons Oilmentioning
confidence: 86%
“…A comprehensive and detailed classification of oil types (oil family typing) in the Danish Central Graben based on evaluation of organofacies-specific biomarkers, stable carbon isotopes and principal component analysis (PCA) was recently published by Petersen et al (2016). In summary, the Danish Central Graben contains several oil families of which the majority can be typed to different facies of the marine shales of the Farsund Formation.…”
Section: Composition and Occurrence Of Coaly Hydrocarbons Oilmentioning
confidence: 99%
See 3 more Smart Citations